A Near‐Process 2D Heat‐Transfer Model for Continuous Slab Casting of Steel. Issue 12 (29th May 2022) - Bernhard, Michael; Santos, Gabriel; Preuler, Lukas; Taferner, Matthias; Wieser, Gerhard; Laschinger, Julian; Ilie, Sergiu; Bernhard, Christian
Abstract : Market requirements on steel products with the highest surface and internal quality demand stimulate a systematic control of the steel solidification behavior during continuous casting (CC). Computational process modeling is increasingly applied to optimize casting practices and calibrate the soft reduction to guarantee the required product quality. Here in this study, an overview of m 2 CAST as a "development platform" for the CC process is presented. This platform consists of a numerical heat‐transfer model, considers results of laboratory experiments in the calculations, for example, thermal analysis and nozzle measuring stand (NMS), and provides the option to use relevant process data. Two case studies on a continuous slab caster at voestalpine Stahl Linz GmbH are investigated. In doing so, thermal boundary conditions obtained by the NMS are implemented, and the simulation trials are validated with temperature measurements of the dragged thermocouple method installed during the casting process. The temperature distribution over the strand width is measured additionally with two pyrometers placed in the straightening zone. Excellent agreement between the calculated strand surface temperature and the measured temperature is obtained. Furthermore, the relevance of considering the roller‐bearing areas in defining the boundary conditions is presented to accurately predict the shape of the crater end. Abstract : The simulation results for the selected case of studies, obtained with m 2 CAST, show reasonable accordance with industrially measured surface temperatures by thermocouples and pyrometers installed at a continuous slab caster. m 2 CAST is a promising tool for optimizing the secondary cooling parameters and adjusting soft reduction settings to enhance the surface and internal quality of continuous cast products.